Recognition and enforcement of foreign court judgments in civil proceedings - Durdona Rixsievna Nazarova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The acceleration of transnational commerce generates complex cross-border legal disputes, elevating the mechanism of exequatur to a primary pillar of international private law. This investigation provides an empirical analysis of the procedural architecture surrounding the recognition and enforcement of foreign judgments within domestic civil proceedings. Systematically evaluating a dataset of 420 exequatur applications processed between January 2021 and December 2025, the research determines how bilateral treaties, international reciprocity, and the public policy exception dictate enforcement probability. Logistic regression modeling reveals a stark jurisdictional dichotomy: judgments from states bound by multilateral or bilateral treaties achieve an 82.4% successful recognition rate, drastically outperforming the 31.6% success rate from non-treaty jurisdictions. The analysis isolates the primary jurisprudential barriers to enforcement, identifying inadequate defendant notification and the expansive interpretation of the public policy defense as dominant catalysts for judicial refusal. Aligning these empirical findings with the 2019 Hague Judgments Convention, this study advocates for the codification of a unified statutory regime governing non-treaty judgments to mitigate legal uncertainty, optimize cross-border litigation efficiency, and secure the functional integrity of transnational civil rights.